Lithium ion battery

The lithium-ion battery design with a polymer solid electrolyte and protective film addresses cycle degradation issues by enhancing stability and conductivity, maintaining battery performance with metal lithium use.

JP2025015073APending Publication Date: 2025-01-30SANYO CHEM IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023118176
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Lithium-ion batteries using metal lithium as an active material face issues with cycle degradation due to lithium dissolution and electrode surface growth, leading to short circuits, and existing protective films and polymer resin layers struggle to balance ionic conductivity and mechanical strength.

Method used

A lithium-ion battery design incorporating a polymer solid electrolyte composed of polyol, diol, and polyisocyanate with specific weight ratios, along with a protective film using crosslinked vinyl monomers, to enhance stability and prevent lithium dissolution.

Benefits of technology

The design significantly reduces cycle degradation, maintaining battery performance even with repeated charging and discharging, ensuring stable ionic conductivity and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015073000001
    Figure 2025015073000001
  • Figure 2025015073000002
    Figure 2025015073000002
  • Figure 2025015073000003
    Figure 2025015073000003
Patent Text Reader

Abstract

To provide a lithium ion battery in which cycle characteristics resist deteriorating even if the charge and discharge have been repeated, even when metallic lithium is used as an electrode.SOLUTION: In the lithium ion battery, metallic lithium and an electrode active material layer which works as a counter electrode are opposed to each other via a polymer solid electrolyte. The polymer solid electrolyte contains a reaction product of a composition which contains a polyol (A-1) having three or more hydroxyl groups, a diol (A-2) and a polyisocyanate (B) having two or more isocyanate groups, and an electrolytic solution (C). A weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is 60 to 80% by weight with reference to a weight of the polymer solid electrolyte, and a storage shear modulus of the polymer solid electrolyte is 10 kPa or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to lithium-ion batteries. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to protect the environment. In the automobile industry, there is hope that the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs) will help reduce carbon dioxide emissions, and efforts are being made to develop secondary batteries for driving motors, which hold the key to putting these vehicles to practical use. As a secondary battery, lithium-ion batteries, which can achieve high energy density and high power density, have been attracting attention.

[0003] When metallic lithium is used as the active material in a lithium-ion battery, it has the advantage of being able to increase the battery capacity; however, there is an issue that as the battery is repeatedly charged and discharged, metallic lithium dissolves, precipitates on the electrode surface, and grows into needle-like particles, causing a short circuit in the battery (deteriorating the cycle characteristics). As a method for solving this problem, for example, Patent Document 1 proposes providing a protective film containing a metal capable of alloying with lithium on metallic lithium, while Patent Document 2 proposes providing a protective layer containing a polymer resin on metallic lithium to suppress lithium precipitation. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-035226 A [Patent Document 2] Special Publication No. 2021-527936 Summary of the Invention [Problem to be solved by the invention]

[0005] However, providing a protective film containing a metal capable of alloying with lithium requires operations such as plating, which poses many problems in terms of equipment for commercialization. It has also been difficult to achieve both ionic conductivity and strength for protective layers containing polymer resins. In addition, all of the above proposals use inorganic solid electrolytes, but lithium deposition also occurs at the interface between the inorganic solid electrolyte and the protective film. Therefore, suppressing lithium deposition at the interface between the solid electrolyte and the protective film and the resulting deterioration of the cycle characteristics of the battery remain issues.

[0006] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a lithium ion battery in which the cycle characteristics are not easily deteriorated even when metallic lithium is used as an electrode, even when the battery is repeatedly charged and discharged. [Means for solving the problem]

[0007] As a result of extensive investigations, the present inventors arrived at the present invention. The present invention is a lithium ion battery in which metallic lithium and an electrode active material layer serving as a counter electrode face each other via a polymer solid electrolyte, the polymer solid electrolyte comprising a reaction product of a composition containing a polyol (A-1) having three or more hydroxyl groups, a diol (A-2), and a polyisocyanate (B) having two or more isocyanate groups, and an electrolyte solution (C), the weight ratio of the electrolyte solution (C) in the polymer solid electrolyte being 60 to 80% by weight based on the weight of the polymer solid electrolyte, and the storage shear modulus of the polymer solid electrolyte being 10 kPa or more. Effect of the Invention

[0008] According to the present invention, it is possible to provide a lithium ion battery in which the cycle characteristics are not easily deteriorated even when the battery is repeatedly charged and discharged, even when metallic lithium is used as an electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The lithium ion battery of the present invention has a structure in which metallic lithium and an electrode active material layer serving as a counter electrode face each other via a polymer solid electrolyte. When metallic lithium functions as a negative electrode, the electrode active material layer serving as a counter electrode is a positive electrode active material layer. The positive electrode active material layer contains a positive electrode active material. The positive electrode active material may be a composite oxide of lithium and a transition metal {composite oxides containing one type of transition metal (e.g., LiCoO2, LiNiO2, LiAlMnO4, LiMnO2, and LiMn2O4), composite oxides containing two types of transition metal elements (e.g., LiFeMnO4, LiNi 1-x Co x O2, LiMn 1-y Co y O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2 and LiNi 0.8 Co 0.15 Al 0.05 O2) and composite oxides containing three or more metal elements [e.g. LiM a M' b M'' c O2(M, M' and M'' are different transition metal elements and satisfy a+b+c=1. For example, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Examples of the conductive polymer include lithium-containing transition metal phosphates (e.g., LiFePO4, LiCoPO4, LiMnPO4, and LiNiPO4), transition metal oxides (e.g., MnO2 and V2O5), transition metal sulfides (e.g., MoS2 and TiS2), and conductive polymers (e.g., polyaniline, polypyrrole, polythiophene, polyacetylene, poly-p-phenylene, and polyvinylcarbazole), and two or more of these may be used in combination. The lithium-containing transition metal phosphate may have some of the transition metal sites substituted with other transition metals.

[0010] When metallic lithium functions as a positive electrode, the electrode active material layer serving as a counter electrode is a negative electrode active material layer. The negative electrode active material layer contains a negative electrode active material. Examples of the negative electrode active material include carbon-based materials [graphite, non-graphitizable carbon, amorphous carbon, resin baked bodies (e.g., phenolic resin, furan resin, etc. baked and carbonized), cokes (e.g., pitch coke, needle coke, petroleum coke, etc.), and carbon fibers, etc.], silicon-based materials [silicon, silicon oxide (SiO x ), silicon-carbon composites (carbon particles whose surfaces are coated with silicon and / or silicon carbide, silicon particles or silicon oxide particles whose surfaces are coated with carbon and / or silicon carbide, and silicon carbide, etc.) and silicon alloys (silicon-aluminum alloy, silicon-lithium alloy, silicon-nickel alloy, silicon-iron alloy, silicon-titanium alloy, silicon-manganese alloy, silicon-copper alloy, silicon-tin alloy, etc.), conductive polymers (e.g. polyacetylene, polypyrrole, etc.), metals (tin, aluminum, zirconium, titanium, etc.), metal oxides (titanium oxide, lithium-titanium oxide, etc.) and metal alloys (e.g. lithium-tin alloy, lithium-aluminum alloy, lithium-aluminum-manganese alloy, etc.), and mixtures of these with carbon-based materials. Among the above-mentioned negative electrode active materials, those that do not contain lithium or lithium ions inside may be subjected to a pre-doping treatment in which lithium or lithium ions are contained in a part or the whole of the negative electrode active material in advance.

[0011] The polymer solid electrolyte in the present invention is present between metallic lithium and an electrode active material layer serving as a counter electrode. The polymer solid electrolyte contains a reaction product of a composition containing a polyol (A-1) having three or more hydroxyl groups, a diol (A-2), and a polyisocyanate (B) having two or more isocyanate groups, and an electrolyte solution (C).

[0012] The polyol (A-1) having three or more hydroxyl groups includes alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol. The polyol (A-1) may be used alone or in combination of two or more kinds. When used alone, it is preferable to use a polyol having three or four hydroxyl groups from the viewpoint of the elasticity of the resulting polymer solid electrolyte.

[0013] Examples of the diol (A-2) include polyether diols, polycarbonate diols, and polyester diols. Examples of polyether diols include polyoxyethylene glycol (PEG), polyoxypropylene glycol (PPG), polyoxyethyleneoxypropylene block copolymer diol, polyoxyethyleneoxytetramethylene block copolymer diol, ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexamethylene glycol, neopentyl glycol, bis(hydroxymethyl)cyclohexane, 4,4'-bis(2-hydroxyethoxy)-diphenylpropane and other low molecular weight glycol ethylene oxide adducts, condensed polyether ester diols obtained by reacting PEG having a number average molecular weight of 2,000 or less with one or more dicarboxylic acids [aliphatic dicarboxylic acids having 4 to 10 carbon atoms (e.g., succinic acid, adipic acid, sebacic acid, etc.), aromatic dicarboxylic acids having 8 to 15 carbon atoms (e.g., terephthalic acid, isophthalic acid, etc.)], and mixtures of two or more of these. Of these, PEG, PPG, polyoxyethyleneoxypropylene block copolymer diol and polyoxyethyleneoxytetramethylene block copolymer diol are preferred, and PEG and PPG are particularly preferred.

[0014] Examples of polycarbonate diols include polycarbonate polyols (e.g., polyhexamethylene carbonate diol) produced by condensing one or more alkylene diols having an alkylene group having 4 to 12 carbon atoms, preferably 6 to 10 carbon atoms, and more preferably 6 to 9 carbon atoms, with a low molecular weight carbonate compound (e.g., dialkyl carbonates having an alkyl group with 1 to 6 carbon atoms, alkylene carbonates having an alkylene group with 2 to 6 carbon atoms, and diaryl carbonates having an aryl group with 6 to 9 carbon atoms, etc.) while causing a dealcoholization reaction.

[0015] Examples of polyester diols include condensed polyester diols obtained by reacting a diol having a number average molecular weight of 1,000 or less and / or a polyether diol having a number average molecular weight of 1,000 or less with one or more of the above-mentioned dicarboxylic acids, and polylactone diols obtained by ring-opening polymerization of lactones having 4 to 12 carbon atoms. Examples of the low molecular weight diols include low molecular weight glycols exemplified in the above polyether diol section. Examples of the polyether diols having a number average molecular weight of 1,000 or less include polyoxypropylene glycol and PTMG. Examples of the lactones include ε-caprolactone and γ-valerolactone. Specific examples of the polyester diols include polyethylene adipate diol, polybutylene adipate diol, polyneopentylene adipate diol, poly(3-methyl-1,5-pentylene adipate) diol, polyhexamethylene adipate diol, polycaprolactone diol, and mixtures of two or more of these.

[0016] From the viewpoint of the mechanical strength of the polymer solid electrolyte, the number average molecular weight of the diol (A-2) is preferably 1,000 to 35,000.

[0017] The number average molecular weight of the diol (A-2) is measured by gel permeation chromatography (hereinafter, sometimes abbreviated as GPC) under the following conditions.

[0018] <Gel permeation chromatography conditions> Equipment: HLC-8320GPC (Tosoh Corporation) Solvent: DMF Standard material: polystyrene Sample concentration: 0.125mg / ml Column stationary phase: TSKgel SuperAW4000, TSKgel SuperAW3000, TSKgel SuperAW2500, 3 columns in series (Tosoh Corporation) Column temperature: 40℃

[0019] Examples of the isocyanate (B) in the present invention include aliphatic isocyanates (b1) having 2 to 18 carbon atoms (excluding carbon atoms in NCO groups, the same applies below), araliphatic isocyanates (b2) having 8 to 15 carbon atoms, aromatic isocyanates (b3) having 6 to 20 carbon atoms, and isocyanate-modified products (b4) of these having an isocyanurate group, a uretoimine group, an allophanate group, a biuret group, a carbodiimide group and / or a uretdione group. One type of isocyanate (B) may be used alone, or two or more types may be used in combination.

[0020] Examples of the aliphatic isocyanate (b1) having 2 to 18 carbon atoms include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), heptamethylene diisocyanate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, 2,2,4- or 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2,6-diisocyanatomethyl capro ... triethyl caproate, bis(2-isocyanatoethyl) fumarate, bis(2-isocyanatoethyl) carbonate, isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexylene-1,2-dicarboxylate, and 2,5- or 2,6-norbornane diisocyanate.

[0021] Examples of the aralkylisocyanate (b2) having 8 to 15 carbon atoms include m- or p-xylylene diisocyanate (XDI), diethylbenzene diisocyanate, and α,α,α',α'-tetramethylxylylene diisocyanate (TMXDI).

[0022] Examples of the aromatic isocyanate (b3) having 6 to 20 carbon atoms include 1,3- or 1,4-phenylene diisocyanate, 2,4- or 2,6-tolylene diisocyanate (TDI), 4,4'- or 2,4'-diphenylmethane diisocyanate (MDI), m- or p-isocyanatophenylsulfonyl isocyanate, 4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatobiphenyl, 3,3'-dimethyl-4,4'-diisocyanatodiphenylmethane, and 1,5-naphthylene diisocyanate.

[0023] Examples of the isocyanate modified product (b4) having an isocyanurate group, a uretoimine group, an allophanate group, a biuret group, a carbodiimide group, and / or a uretdione group include a modified product of MDI having a uretoimine group, a modified product of HDI having a biuret group, and a modified product of HDI having an isocyanurate group.

[0024] As the isocyanate (B), from the viewpoint of elasticity and stretchability of the resulting polymer solid electrolyte, MDI is preferred, and polymeric MDI is more preferred. Polymeric MDI is a mixture of monomeric MDI with various isomer contents and polynuclear MDI with several structures.

[0025] From the viewpoint of elasticity of the polymer solid electrolyte, the weight proportion of the polyol (A-1) having three or more hydroxyl groups is preferably 0.1 to 1.0% by weight based on the weight of the polymer solid electrolyte. Similarly, from the viewpoint of the elasticity of the polymer solid electrolyte, the weight proportion of the diol (A-2) is preferably 20 to 40% by weight based on the weight of the polymer solid electrolyte. Similarly, from the viewpoint of elasticity of the polymer solid electrolyte, the weight proportion of the polyisocyanate (B) having two or more isocyanate groups is preferably 1.0 to 5% by weight based on the weight of the polymer solid electrolyte.

[0026] The electrolytic solution (C) in the present invention comprises an electrolyte and an electrolytic solution solvent. The electrolyte can be any known lithium salt used in lithium ion batteries, and examples of such electrolytes include inorganic acid lithium salt electrolytes such as LiCF3SO3, LiPF6, LiBF4, LiSbF6, LiAsF6, and LiClO4; sulfonylimide electrolytes such as LiFSi, LiN(FSO2)2, LiN(CF3SO2)2, LiN(C2F5SO2)2, and LiC2F3NO4S2 (LiTFSI); and sulfonylmethide electrolytes having a fluorine atom such as LiC(CF3SO2)3. From the viewpoint of thermal stability and hydrolysis resistance, the electrolyte is preferably a sulfonylimide electrolyte.

[0027] The electrolyte solvent preferably has a flash point of 100° C. or higher. When the flash point of the electrolyte solvent is 100° C. or higher, the safety (flame retardancy) of the polymer solid electrolyte is improved. As the electrolyte solvent, a mixture of multiple solvents may be used. As long as the electrolyte solvent after mixing has a flash point of 100°C, a solvent having a flash point of less than 100°C may be included. Examples of the electrolyte solvent include dimethyl carbonate, ethylene carbonate (EC), ethyl methyl carbonate, diethyl carbonate, ethyl propyl carbonate (EPC), dipropyl carbonate (DPC), dipropylene glycol dimethyl ether, tripropylene glycol dimethyl ether, tetrapropylene glycol dimethyl ether, diglyme, triglyme, tetraglyme, and sulfolane.

[0028] In this specification, the flash points of the electrolyte solvent and the electrolyte are temperatures measured by the tag seal method specified in JIS K 2265-1-2007.

[0029] The weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is 60 to 80% by weight based on the weight of the polymer solid electrolyte. If the weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is less than 60% by weight based on the weight of the polymer solid electrolyte, the ion conductivity of the polymer solid electrolyte decreases, and if the weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is more than 80% by weight based on the weight of the polymer solid electrolyte, the mechanical strength of the polymer solid electrolyte is insufficient. From the viewpoint of achieving both ion conductivity and strength of the polymer solid electrolyte, the weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is preferably 65 to 80% by weight based on the weight of the polymer solid electrolyte.

[0030] The polymer solid electrolyte has a storage shear modulus of 10 kPa or more. If the polymer solid electrolyte has a storage shear modulus of less than 10 kPa, the electrode shape becomes unstable. From the viewpoints of electrode flexibility and electrolyte retention, the polymer solid electrolyte has a storage shear modulus of preferably 10 to 100 kPa, more preferably 10 to 61 kPa. The storage shear modulus of the polymer solid electrolyte can be adjusted by the weight ratio of the polyol (A-1) having three or more hydroxyl groups and the weight ratio of the electrolytic solution (C) in the polymer solid electrolyte.

[0031] The storage shear modulus in the present invention was measured by the following method. All the materials constituting the polymer solid electrolyte were filled into a silicon mold with a diameter of 8 mm and a thickness of 1 mm, and cured at 80°C for 3 hours to form a measurement sample. The measurement sample was sandwiched between parallel plates with a diameter of 8 mm in an Anton Paar rheometer "MCR-802" and the plate gap was adjusted so that the normal force was 1.0 N when the temperature was controlled at 25°C. Then, measurements were performed at a rotational strain of 2% and a shear frequency of 0.01 to 10 Hz.

[0032] In addition to the above-mentioned components, the polymer solid electrolyte of the present invention may contain additives used in ordinary polymer compounds within the scope of the present invention. Examples of the additives include stabilizers such as antioxidants, heat stabilizers, and light resistance stabilizers; ultraviolet absorbers; fillers such as inorganic fillers and organic fillers; lubricants; release agents; plasticizers; and antistatic agents.

[0033] From the viewpoint of mechanical properties, the thickness of the polymer solid electrolyte is preferably 30 to 150 μm. The thickness of the polymer solid electrolyte can be adjusted by the molding conditions.

[0034] The polymer solid electrolyte of the present invention can be produced by mixing all the components constituting the polymer solid electrolyte, and then heating the mixture to 50° C. to 100° C. to harden it.

[0035] The lithium ion battery of the present invention preferably further comprises a protective film between the metallic lithium and the polymer solid electrolyte, which further improves the cycle characteristics of the lithium ion battery.

[0036] The protective film preferably contains a copolymer having a crosslinkable vinyl monomer as an essential constituent monomer and an electrolytic solution (D). Examples of the crosslinkable vinyl monomer include divinylbenzene, ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol penta- or hexa(meth)acrylate, etc. Here, (meth)acrylate means acrylate or methacrylate.

[0037] From the viewpoint of mechanical properties of the protective film, it is more preferable that the crosslinkable vinyl monomer contains a monomer having four or more radically polymerizable functional groups selected from the group consisting of vinyl groups, acryloyl groups, and methacryloyl groups. Specific examples include dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, etc. By containing a monomer having four or more radically polymerizable functional groups, the mechanical strength is improved and the growth of dendrites in a direction perpendicular to the electrode due to dissolution and precipitation accompanying repeated charging and discharging of Li metal can be suppressed.

[0038] From the viewpoint of the mechanical properties and film formability of the protective film, the weight of the crosslinkable vinyl monomer in the protective film is preferably 12 to 18% by weight based on the total weight of the monomers constituting the copolymer and the electrolytic solution (D).

[0039] The copolymer preferably contains, as a monomer constituting the copolymer, other polymerizable vinyl monomers (E) in addition to the crosslinkable vinyl monomers. Examples of the other polymerizable vinyl monomers (E) include copolymerizable vinyl monomers (e1) that do not contain active hydrogen atoms.

[0040] Examples of (e1) include the following (e11) to (e14). (e11) Hydrocarbyl (meth)acrylate the hydrocarbyl group being an aliphatic [carbon number (hereinafter abbreviated as C) of 1 to 25 (preferably 4 to 18), such as an alkyl group [methyl, ethyl, n- or i-propyl, n-, i-, sec- or t-butyl, n-, i-, sec-, t- or neopentyl, n-octyl, 2-ethylhexyl, nonyl, decyl, lauryl, tridecyl, myristyl, cetyl, stearyl group, etc.] and an alkenyl group [ethenyl, propenyl, butenyl, hexenyl, decenyl, oleyl group, etc.]], an alicyclic [C4 to 18, such as cyclobutyl, cyclopentyl, and cyclohexyl groups] and an aromatic aliphatic [C7 to 18, such as benzyl and phenylethyl groups] carbyl group, etc.;

[0041] (e12) Poly(n=2-30)oxyalkylene alkyl (C1-18) ether (meth)acrylate (Meth)acrylate of an adduct of 10 moles of ethylene oxide (hereinafter abbreviated as EO) to methanol, (meth)acrylate of an adduct of 10 moles of propylene oxide (hereinafter abbreviated as PO) to methanol, etc.;

[0042] (e13) Nitrogen-containing vinyl monomer (e131) C3-20 tertiary or quaternary nitrogen-containing (meth)acrylamide compounds Tertiary nitrogen-containing (meth)acrylamide compounds [dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, etc.]; Quaternary nitrogen-containing vinyl compounds [Quaternized products of the above tertiary nitrogen-containing vinyl compounds (using quaternizing agents such as methyl chloride, dimethyl sulfate, benzyl chloride, dimethyl carbonate, etc. (4th grade, etc.)

[0043] (E132) Tertiary or quaternary nitrogen-containing (meth)acrylates Tertiary nitrogen-containing [dialkyl (C1-4) aminoalkyl (C1-4) (meth)acrylates [N,N-dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate, etc.], heterocycle-containing (meth)acrylates [morpholinoethyl (meth)acrylate, etc.], etc.]; Quaternary nitrogen-containing ((meth)acrylates [quaternized products of the above-mentioned tertiary amino group-containing (meth)acrylates (those quaternized using the above-mentioned quaternizing agents)], etc.];

[0044] (E133) Heterocyclic vinyl compounds Pyridine compounds (C7-14, for example, 2- or 4-vinylpyridine), imidazole compounds (C5-12, for example, N-vinylimidazole), pyrrole compounds (C6-13, for example, N-vinylpyrrole), etc.; (E134) Nitrile group-containing vinyl compounds C3-15 nitrile group-containing vinyl compounds, such as (meth)acrylonitrile, cyanostyrene, and cyanoalkyl (C1-4)acrylates; (E135) Other nitrogen-containing vinyl compounds Nitro group-containing vinyl compounds (C8-16, e.g., nitrostyrene);

[0045] (e14) Unsaturated hydrocarbons (E141) Aliphatic unsaturated hydrocarbons C2-18 or higher olefins [ethylene, propylene, butene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene, etc.], C4-10 or higher dienes [butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, 1,7-octadiene, etc.], etc.; (E142) Alicyclic unsaturated hydrocarbons Cyclic unsaturated hydrocarbons with C4 to C18 or more, such as cyclohexene, (di)cyclopentadiene, pinene, limonene, and indene; (E143) Aromatic unsaturated hydrocarbons Aromatic unsaturated hydrocarbons with C8 to C20 or more, such as styrene, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, and benzylstyrene;

[0046] (e15) Vinyl esters, vinyl ethers, vinyl ketones, unsaturated dicarboxylic acid diesters (e151) vinyl ester Aliphatic vinyl esters (C4-15, e.g. vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl adipate, isopropenyl acetate, vinyl methoxyacetate, vinyl benzoate); Aromatic vinyl esters (C9-20, e.g., diallyl phthalate, methyl-4-vinyl benzoate, acetoxystyrene);

[0047] (e152) vinyl ether aliphatic vinyl ethers (C3-15, for example, vinyl alkyl (C1-10) ethers [vinyl methyl ether, vinyl butyl ether, vinyl 2-ethylhexyl ether, etc.], vinyl alkoxy (C1-6) alkyl (C1-4) ethers [vinyl-2-methoxyethyl ether, methoxybutadiene, 3,4-dihydro-1,2-pyran, 2-butoxy-2'-vinyloxydiethyl ether, vinyl-2-ethylmercaptoethyl ether, etc.], poly(2-4) (meth)allyloxyalkanes (C2-6) [diallyloxyethane, triallyloxyethane, tetraallyloxybutane, tetramethallyloxyethane, etc.]); Aromatic vinyl ethers (C8-20, e.g. vinyl phenyl ether, phenoxystyrene);

[0048] (E153) Vinyl ketone Aliphatic vinyl ketones (C4-25, e.g. vinyl methyl ketone, vinyl ethyl ketone); Aromatic vinyl ketones (C9-21, e.g. vinyl phenyl ketone); (E154) Unsaturated dicarboxylic acid diesters C4-34 unsaturated dicarboxylic acid diesters, for example, di(cyclo)alkyl fumarate, di(cyclo)alkyl maleate (in each case, the two (cyclo)alkyl groups represent a C1-22 linear, branched or alicyclic group).

[0049] From the viewpoint of the mechanical properties of the protective film and the affinity with metallic lithium, the other polymerizable vinyl monomer (E) is preferably one in which the polymer obtained by the polymerization reaction of the monomer has a glass transition temperature of 25° C. or higher and an SP value of the monomer of 6.8 or higher, and more preferably one in which the polymer has a glass transition temperature of 45° C. or higher and an SP value of the monomer of 8 or higher. For example, isobornyl methacrylate, methyl methacrylate, vinyl benzoic acid and 3-(dimethylaminopropyl) methacrylamide are preferred.

[0050] As the electrolytic solution (D), the same electrolytic solution as the above-mentioned electrolytic solution (C) can be used. The electrolytic solution (D) and the electrolytic solution (C) may be the same or different.

[0051] From the viewpoint of achieving both mechanical properties and ionic conductivity of the protective film, the weight proportion of the electrolytic solution (D) in the protective film is preferably 40 to 60% by weight based on the total weight of the monomers constituting the copolymer and the electrolytic solution (D).

[0052] From the viewpoint of compatibility between the copolymer and the electrolyte solution (D), the absolute value of the difference between the SP value of the electrolyte solution (D) and the SP value of each of the constituent monomers of the copolymer in the protective film is 4.9 (cal / cm 3 ) 1 / 2 The electrolytic solution (D) may be a mixture of two or more kinds, in which case the SP value of the electrolytic solution (D) is a weighted average of values ​​calculated by the following method. The SP value of the electrolytic solution (D) may be considered to be the same as the SP value of the electrolytic solution solvent constituting the electrolytic solution (D).

[0053] In this application, the SP value (solubility parameter) [unit: (cal / cm 3 ) 1 / 2 ] is a value calculated by the method described in formula (28) on page 153 of the Fedors method (Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, pp. 147-154) using the values ​​(heat of vaporization and molar volume at 25°C of atoms or functional groups) described on page 152 (Table. 5) of the Fedors method. Specifically, it can be calculated by applying the values ​​of Δei and Δvi described in Table 1 below, which are parameters of the Fedors method, to the following formula (1) using the values ​​corresponding to the types of atoms and atomic groups in the molecular structure. SP value = (ΣΔei / ΣΔvi) 1 / 2 (1) In the above formula, ΣΔei (unit: cal / mol) is the cohesive energy density (unit: cal / mol), and ΣΔvi is the molecular volume (unit: cm 3 / mol).

[0054] [Table 1]

[0055] From the viewpoint of the stability of the electrode, the protective film preferably has a storage shear modulus of 10 to 32 MPa. The storage shear modulus of the protective film can be adjusted by the weight ratio of the crosslinkable vinyl monomer in the protective film or the weight ratio of the electrolytic solution (D).

[0056] From the viewpoint of mechanical properties, the thickness of the protective film is preferably 10 to 15 μm. The thickness of the protective film can be adjusted by the molding conditions.

[0057] In addition to the above-mentioned components, the protective film of the present invention may contain additives used in ordinary polymer compounds within the scope of the present invention. Examples of additives include stabilizers such as antioxidants, heat stabilizers, and light resistance stabilizers; UV absorbers; fillers such as inorganic fillers and organic fillers; lubricants; release agents; plasticizers; antistatic agents, etc.

[0058] The protective film in the present invention can be produced by mixing all the components constituting the protective film, and then heating the mixture to 50° C. to 100° C. to cure it. EXAMPLES

[0059] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.

[0060] <Preparation of electrolyte> A stirrer and 38.3 parts by weight of tripropylene glycol dimethyl ether (Tokyo Chemical Industry Co., Ltd.) were added to a reaction vessel that had been dried for one day in an environment with a temperature of 19°C and a dew point of -60°C dp, and the mixture was stirred with a magnetic stirrer. 15.1 parts by weight of lithium (bisfluorosulfonyl)imide (Kishida Chemical Co., Ltd.) and 16.4 parts by weight of ethylene carbonate (Tokyo Chemical Industry Co., Ltd.) were added thereto, dissolved, and homogenized to prepare an electrolytic solution.

[0061] (Preparation of Polymer Solid Electrolyte: Production Example 1) To 69.8 parts by weight of the prepared electrolyte, 0.4 parts by weight of a trifunctional propylene oxide adduct (Sanyo Chemical Industries, Ltd., Sannix GP-250), 1.2 parts by weight of a bifunctional polypropylene oxide (Sanyo Chemical Industries, Ltd., Sannix PPG-600), and 25.3 parts by weight of a bifunctional polypropylene oxide (Sanyo Chemical Industries, Ltd., Sannix PPG-4000) were added. Then, 0.2 parts by weight of a bismuth-based metal catalyst (Nitto Chemical Industries, Ltd., Neostan U-600) was added and stirred for 10 minutes to obtain a transparent and uniform polyalcohol solution. 3.0 parts by weight of polymeric MDI (Millionate MR-200, manufactured by Tosoh Corporation) was added to the prepared polyalcohol solution and stirred for 5 minutes to obtain a pale yellow liquid. The obtained pale yellow liquid was degassed under reduced pressure at 19°C for 30 minutes in a bell jar to prepare a polymer electrolyte precursor. The polymer electrolyte precursor was gently poured into a 5cm x 10cm square PP tray, and the precursor was spread over the entire bottom of the tray. The temperature was then adjusted to 80°C for 3 hours in a thermostatic chamber with a leveled surface. After the temperature adjustment was completed, the sample was peeled off from the PP tray to obtain a pale yellow transparent polymer solid electrolyte (K-1). The thickness of the polymer solid electrolyte measured with a thickness gauge was 500μm.

[0062] (Preparation of Polymer Solid Electrolyte: Production Examples 2 to 4 and Comparative Production Examples 1 to 5) As shown in Table 2, polymer solid electrolytes according to Production Examples 2 to 4 and Comparative Production Examples 1 to 5 were prepared in the same manner as in Production Example 1, except that the various constituent types and weight ratios were changed.

[0063] [Table 2]

[0064] Details of the abbreviations listed in Table 2 are as follows: PEG-2000: Polyethylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] PE-68: "Newpol PE-68" [manufactured by Sanyo Chemical Industries, Ltd.] PPG-4000: Polypropylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] PEG-200: Polyethylene glycol [Sanyo Chemical Industries, Ltd.] PPG-600: Polypropylene glycol [manufactured by Sanyo Chemical Industries, Ltd.] EC: Ethylene carbonate [Tokyo Chemical Industry Co., Ltd.] PC: Propylene carbonate [Tokyo Chemical Industry Co., Ltd.] DEC: Diethyl carbonate [Tokyo Chemical Industry Co., Ltd.] TGDE: Triethylene glycol dimethyl ether [Kishida Chemical Co., Ltd.] G4: Tetraethylene glycol dimethyl ether (tetraglyme) [Kishida Chemical Co., Ltd.] PG3: Tripropylene glycol dimethyl ether [FUJIFILM Wako Pure Chemical Industries, Ltd.] LiPF6: Lithium hexafluorophosphate LiFSI: Lithium bis(fluorosulfonyl)imide LiTFSI: Lithium bis(trifluoromethylsulfonyl)imide

[0065] <Measurement of storage shear modulus> The polymer electrolyte precursor was filled into a silicon mold with a diameter of 8 mm and a thickness of 1 mm, and cured at 80°C for 3 hours to form a measurement sample. The measurement sample was sandwiched between parallel plates with a diameter of 8 mm in an Anton Paar rheometer "MCR-802" and the plate gap was adjusted so that the normal force was 1.0 N when the temperature was controlled at 25°C. Then, measurements were performed at a rotational strain of 2% and a shear frequency of 0.01 to 10 Hz. The results are shown in Table 3.

[0066] <Measurement of electrolyte retention rate and 1 atmosphere self-sustaining ability> The obtained solid polymer electrolyte was cut into 20 mm x 20 mm squares to prepare samples for evaluating electrolyte retention. Three PP separators ("Celgard #3501") cut into 30 mm x 30 mm squares were placed on both sides of the sample, and the sample was sandwiched between 10 mm thick, 60 mm x 100 mm square stainless steel plates. A weight was placed on the upper stainless steel plate so that the load on the sample was 4 kg, and the temperature was controlled at 25 ° C for 48 hours. After the temperature control was completed, six separators were taken out, and the electrolyte retention was calculated from the weight before evaluation W0, the weight after evaluation W1, and the initial weight of the sample S0 using the following formula. Electrolyte retention rate = (1-((W1-W0) / S0))×100(%) After the evaluation, the samples were measured on all four sides with a vernier caliper to check for deformation and for the presence of cracks, etc. The results are shown in Table 3.

[0067] <Ionic conductivity evaluation> The obtained solid polymer electrolyte was punched into a circle with a diameter of 18 mm to prepare a sample for evaluating ionic conductivity. The sample was sandwiched between two pieces of Li metal (manufactured by Honjo Metals Co., Ltd., Li-Foil: thickness: 0.5 mm) punched into a circle with a diameter of 16 mm, and a stainless steel metal electrode was placed on the outside. Impedance measurements were performed in a constant temperature bath controlled at 25°C using an electrochemical measurement device "VSP-300" made by BioLogic Co., Ltd. in the frequency range of 7 MHz to 1 Hz. The semicircle on the high frequency side in the obtained Nyquist plot was taken as the bulk resistance R of the sample, and the ionic conductivity δ was calculated from the thickness d of the sample and the opposing area A with the Li metal using the following formula. The results are shown in Table 3. δ = d / (R × A)

[0068] <Current density measurement> The degree of current that the polymer solid electrolyte can stably pass was evaluated using chronopotentiometry. The obtained polymer solid electrolyte was punched out into a circle with a diameter of 18 mm to prepare a sample for evaluating the current density. The sample was sandwiched between two sheets of lithium metal (Li-Foil: thickness 0.5 mm, manufactured by Honjo Metals Co., Ltd.) punched out into a circle with a diameter of 16 mm, and a stainless steel metal electrode was placed on the outside. Next, using an electrochemical measurement device (VSP-300) made by BioLogic Corporation, the current density was measured at 0.01 mA / cm in a thermostatic chamber adjusted to 25°C. 2 The current density was then maintained at -0.01mA / cm for 1 hour to confirm whether the voltage stabilized. If the voltage stabilized, it can be said that ion conduction within the sample was sufficient. 2 The current density was then increased by alternating between + and -, and the measurement was terminated when the voltage reached ±2V. The current density measured just before the voltage reached ±2V was determined as the limit current density that could be output. The results are shown in Table 3.

[0069] [Table 3]

[0070] (Preparation of protective film: Production Example 5) Dipentaerythritol hexaacrylate (Sanyo Chemical Industries, Ltd., Neomer DA-600) 15 parts by weight, vinyl benzoate (Tokyo Chemical Industry Co., Ltd.) 35 parts by weight, ethylene carbonate 17 parts by weight, propylene carbonate (Tokyo Chemical Industry Co., Ltd.) 17 parts by weight, LiFSI 16 parts by weight, and 2,2'-azobis(2,4-dimethylvaleronitrile) (FUJIFILM Wako Pure Chemical Industries, Ltd.: V-65) 0.01 parts by weight were mixed in a screw tube to obtain a protective film precursor. The curing time of the protective film precursor was measured at 80°C with a rheometer and was found to be 45 minutes. 1.0 parts of the protective film precursor was gently poured into 1 mm thick silicon molds with various inner diameters, and the temperature was controlled at 80°C for 1 hour in a thermostatic chamber with a leveled surface. After the temperature control was completed, the material was removed from the silicon mold to obtain a transparent protective film.

[0071] (Preparation of protective film: Examples 6 to 10) As shown in Table 4, protective films according to Production Examples 6 to 10 were prepared in the same manner as Production Example 5, except that the various constituent types and weight ratios were changed.

[0072] [Table 4]

[0073] <Measurement of storage shear modulus> The protective film obtained by removing it from the 8 mm diameter silicon mold was sandwiched between 8 mm diameter parallel plates in an Anton Paar rheometer "MCR-802" and the plate gap was adjusted so that the normal force was 1.0 N at a temperature of 25°C. Then, measurements were performed at a rotational strain of 2% and a shear frequency of 1 Hz. The results are shown in Table 5.

[0074] <Measurement of electrolyte retention rate> The protective film obtained by removing it from the 16 mm diameter silicon mold was used as a measurement sample. Three PP separators ("Celgard #3501") cut into 30 mm x 30 mm squares were placed on both sides of the sample, and the sample was sandwiched between 10 mm thick, 60 mm x 100 mm square stainless steel plates. A weight was placed on the upper stainless steel plate so that the load on the sample was 4 kg, and the temperature was controlled at 25 ° C for 48 hours. After the temperature control was completed, six separators were taken out, and the electrolyte retention rate was calculated using the following formula from the weight before evaluation W0, the weight after evaluation W1, and the initial weight of the sample S0. The results are shown in Table 5. Electrolyte retention rate = (1-((W1-W0) / S0))×100(%)

[0075] <Ionic conductivity evaluation> The protective film obtained by removing it from the silicon mold with a diameter of 8 mm was used as a measurement sample. The sample was placed inside a PP ring processed to an inner diameter of 10 mm and an outer diameter of 18 mm, and two lithium metal sheets punched into a circular shape with a diameter of 16 mm were sandwiched between the top and bottom, and a stainless steel metal electrode was placed on the outside. Impedance measurements were performed in a constant temperature bath controlled at 25°C using an electrochemical measurement device (VSP-300) made by BioLogic in the frequency range of 7 mHz to 1 Hz. The semicircle on the high frequency side in the obtained NyquiSt plot was taken as the bulk resistance R of the sample, and the ionic conductivity δ was calculated from the thickness d of the sample and the area A facing the lithium metal using the following formula. The results are shown in Table 5. δ = d / (R × A)

[0076] <Measurement of the number of lithium deposition cycles> The protective film obtained by removing it from the 16 mm diameter silicon mold was used as a measurement sample. Metallic lithium was punched out into a circle with a diameter of 16 mm, and the metallic lithium, protective film, and metallic lithium were placed in a CR2032 coin cell in this order. The resulting coin cell was measured using an electrochemical measurement device (VSP-300) made by Biologic Corporation, with a measurement of ±2.0 mA / cm 2 The current density was alternately applied for 1 hour each, and the number of cycles at which the overvoltage decreased (presumably due to a decrease in resistance caused by an increase in the reaction surface area due to the dissolution and deposition of metallic lithium) was defined as the number of lithium deposition cycles. The results are shown in Table 5.

[0077] [Table 5]

[0078] (Preparation of Lithium-Ion Battery: Example 1) 82 parts by weight of lithium iron phosphate (Merck, LiFePO4), 12 parts by weight of acetylene black (Denka Co., Ltd., Denka Black: average particle size 35 nm), and 46 parts by weight of polyvinylidene fluoride in N-methylpyrrolidone (hereinafter abbreviated as NMP) solution (Kuraray Co., Ltd., KF Polymer L) were placed in a dedicated container for a kneading device (Thinky Co., Ltd., Awatori Rentaro) and kneaded for 1 minute at 2000 rpm. Next, 44 parts by weight of NMP was added and kneaded for 1 minute at 2000 rpm, and this operation was repeated 5 times to obtain a slurry of an electrode composition. The obtained slurry was applied to an aluminum foil with a squeegee, and then dried with hot air at 120℃ for 1 hour in a parallel dryer to obtain an average coating weight of 2.3mg_LFP / cm. 2 The electrodes were obtained.

[0079] The thickness of the obtained electrode was measured, and the polymer solid electrolyte precursor (composition: K-1) prepared in Production Example 1 was applied using a squeegee with a gap of 33 μm relative to the thickness of the electrode. The temperature was then controlled at 80°C for 3 hours in a thermostatic chamber with good equilibrium to produce a polymer solid electrolyte on the electrode. The thickness of the polymer solid electrolyte was 30 μm.

[0080] The electrode with the solid polymer electrolyte was punched out into a circle with a diameter of 18 mm to be used as the positive electrode. Next, a metal lithium punched out into a circle with a diameter of 16 mm was placed on the solid polymer electrolyte and housed in a CR2032 coin cell to prepare a lithium ion battery.

[0081] (Preparation of Lithium-Ion Battery: Example 2) A lithium ion battery according to Example 2 was produced in the same manner as in Example 1, except that the composition of the polymer solid electrolyte used was changed from (K-1) to (K-3).

[0082] (Preparation of Lithium-Ion Battery: Example 3) Metallic lithium was placed on a flat coating table in an argon glove box, and the protective film precursor (composition: H-1) prepared in Production Example 5 was applied onto the metallic lithium using a bar coater No. 7 manufactured by AS ONE. The metallic lithium coated with the protective film precursor was left to stand for 1 hour in a thermostatic chamber at 80°C installed in the glove box to form a protective film on the metallic lithium. The appearance of the formed protective film was uniform, and the film thickness was measured to be 13 μm.

[0083] The thickness of the electrode prepared in Example 1 was measured, and the polymer solid electrolyte precursor (composition: K-1) prepared in Production Example 1 was applied using a squeegee with a gap of 73 μm relative to the thickness of the electrode. The temperature was then adjusted to 80° C. for 3 hours in a thermostatic chamber with good equilibrium, to prepare a polymer solid electrolyte on the electrode. The thickness of the polymer solid electrolyte was 70 μm. The electrode with the polymer solid electrolyte was punched out into a circle with a diameter of 18 mm to form a positive electrode. Next, a metallic lithium with a protective film punched out into a circle with a diameter of 16 mm was placed so that the protective film and the polymer solid electrolyte were directly overlapped, and the resultant was housed in a CR2032 coin cell to form a lithium ion battery.

[0084] (Preparation of Lithium-Ion Battery: Example 4) Metallic lithium was placed on a flat coating table in an argon glove box, and the protective film precursor (composition: H-2) prepared in Production Example 6 was applied onto the metallic lithium using a bar coater No. 7 manufactured by AS ONE. The metallic lithium coated with the protective film precursor was left to stand for 1 hour in a thermostatic chamber at 80°C installed in the glove box to form a protective film on the metallic lithium. The appearance of the formed protective film was uniform, and the film thickness was measured to be 13 μm.

[0085] The thickness of the electrode prepared in Example 1 was measured, and the polymer solid electrolyte precursor (composition: K-3) prepared in Production Example 3 was applied using a squeegee with a gap of 33 μm increased relative to the thickness of the electrode. The temperature was then controlled at 80° C. for 3 hours in a thermostatic chamber with good parallelism to prepare a polymer solid electrolyte on the electrode. The thickness of the polymer solid electrolyte was 30 μm. The electrode provided with the polymer solid electrolyte was punched out into a circle with a diameter of 18 mm to form a positive electrode.

[0086] The polymer solid electrolyte precursor (composition: K-3) prepared in Production Example 3 was applied to a PET release film with a gap of 120 μm, and the temperature was controlled at 80°C for 3 hours in a thermostatic chamber with a parallel balance, and then the film was released from the PET release film to obtain a polymer solid electrolyte membrane (composition: K-3). The thickness of the obtained polymer solid electrolyte membrane was 120 μm. The solid polymer electrolyte membrane was punched out into a circle with a diameter of 18 mm, and placed so as to overlap the solid polymer electrolyte of the positive electrode. Next, a metallic lithium with a protective film punched out into a circle with a diameter of 16 mm was placed so that the protective film and the solid polymer electrolyte were directly overlapped, and the lithium was placed in a CR2032 coin cell to create a lithium-ion battery.

[0087] (Preparation of Lithium-Ion Batteries: Examples 5 to 8) Lithium ion batteries according to Examples 5 to 8 were produced in the same manner as in Example 3, except that the compositions and film thicknesses of the polymer solid electrolyte precursor and the protective film precursor were changed as shown in Table 6. In Examples 6 and 8, a bar coater No. 8 manufactured by AS ONE was used to coat the protective film precursor onto the metallic lithium.

[0088] (Production of Lithium-Ion Battery: Comparative Example 1) Metallic lithium was placed on a flat coating table in an argon glove box, and the protective film precursor (composition: H-1) prepared in Production Example 5 was applied onto the metallic lithium using a bar coater No. 7 manufactured by AS ONE. The metallic lithium coated with the protective film precursor was left to stand for 1 hour in a thermostatic chamber at 80°C installed in the glove box to form a protective film on the metallic lithium. The appearance of the formed protective film was uniform, and the film thickness was measured to be 13 μm.

[0089] The thickness of the electrode prepared in Example 1 was measured, and the polymer solid electrolyte precursor (composition: K'-1) prepared in Comparative Production Example 1 was applied using a squeegee with a gap of 33 μm increased relative to the thickness of the electrode. The temperature was then controlled at 80° C. for 3 hours in a thermostatic chamber with good parallelism to prepare a polymer solid electrolyte on the electrode. The thickness of the polymer solid electrolyte was 30 μm. The electrode provided with the polymer solid electrolyte was punched out into a circle with a diameter of 18 mm to form a positive electrode.

[0090] The polymer solid electrolyte precursor (composition: K'-1) prepared in Comparative Production Example 1 was applied to a PET release film with a gap of 90 μm, and after regulating the temperature at 80°C for 3 hours in a thermostatic chamber with a parallel balance, it was released from the PET release film to obtain a polymer solid electrolyte membrane (composition: K'-1). The thickness of the obtained polymer solid electrolyte membrane was 90 μm. The solid polymer electrolyte membrane was punched out into a circle with a diameter of 18 mm, and placed so as to overlap the solid polymer electrolyte of the positive electrode. Next, a metallic lithium with a protective film punched out into a circle with a diameter of 16 mm was placed so that the protective film and the solid polymer electrolyte were directly overlapped, and the lithium was placed in a CR2032 coin cell to create a lithium-ion battery.

[0091] (Fabrication of Lithium-Ion Battery: Comparative Example 2) The thickness of the electrode prepared in Example 1 was measured, and the protective film precursor (composition: H-1) prepared in Production Example 5 was applied instead of the polymer solid electrolyte precursor using a squeegee with a gap of 65 μm relative to the thickness of the electrode. The temperature was then adjusted to 80° C. for 1 hour in a thermostatic chamber with good equilibrium to form a polymer solid electrolyte film on the electrode. The thickness of the polymer solid electrolyte was 50 μm. The obtained electrode with the polymer solid electrolyte was punched into a circle with a diameter of 18 mm to form a positive electrode. Next, metallic lithium with a protective film (composition: H-1) prepared in Example 3, which was punched into a circle with a diameter of 16 mm, was placed so that the protective film and the positive electrode directly overlapped each other, and the resultant was housed in a CR2032 coin cell to form a lithium ion battery.

[0092] (Fabrication of Lithium-Ion Battery: Comparative Example 3) The electrode prepared in Example 1 was punched out into a circle with a diameter of 16 mm to form a positive electrode. 10 μL of an electrolyte prepared by mixing EC, DEC and LiPF6 in a ratio of 30:50:20% by weight was injected into the electrode using a micropipette. Next, two sheets of Celgard 2500 (made of PP, thickness 25 μm) punched out into a circle with a diameter of 18 mm were laminated, and 10 μL of the electrolyte was injected into the electrode. Next, metallic lithium punched out into a circle with a diameter of 16 mm was laminated and stored in a CR2032 coin cell to form a lithium ion battery.

[0093] <Measurement of durability cycles> The resulting lithium-ion battery was evaluated for charge and discharge using a BioLogic charge and discharge system "BCS-805". The charging conditions were 0.04 mA / cm 2 Constant current charging up to 4.0V, discharging at 0.04mA / cm 2 A constant current discharge was performed to 2.0 V at 100 mAh. This charge / discharge cycle constitutes one cycle. When the battery no longer reached 4.0 V even after 15 hours of charging, it was determined that a partial short circuit had occurred inside the battery. The number of cycles immediately before the battery no longer reached 4.0 V even after charging was regarded as the number of endurance cycles. The results are shown in Table 6.

[0094] [Table 6] [Industrial Applicability]

[0095] The lithium ion battery of the present invention is used in fuel cells, water electrolysis devices, hydrohalic acid electrolysis devices, salt electrolysis devices, oxygen concentrators, humidity sensors, gas sensors, etc. It is particularly suitable for use as a polymer electrolyte fuel cell as an on-board power source or a home power source.

Claims

1. A lithium ion battery in which metallic lithium and an electrode active material layer serving as a counter electrode face each other via a polymer solid electrolyte, the polymer solid electrolyte comprises a reaction product of a composition including a polyol (A-1) having three or more hydroxyl groups, a diol (A-2), and a polyisocyanate (B) having two or more isocyanate groups, and an electrolytic solution (C); The weight ratio of the electrolytic solution (C) in the polymer solid electrolyte is 60 to 80% by weight based on the weight of the polymer solid electrolyte, A lithium ion battery, characterized in that the storage shear modulus of the polymer solid electrolyte is 10 kPa or more.

2. 2. The lithium ion battery according to claim 1, wherein the polyisocyanate (B) is polymeric diphenylmethane diisocyanate.

3. A protective film is further provided between the metallic lithium and the polymer solid electrolyte, the protective film contains a copolymer having a crosslinkable vinyl monomer as an essential constituent monomer and an electrolytic solution (D), The protective film has a storage shear modulus of 10 to 32 MPa; 2. The lithium ion battery according to claim 1, wherein the protective film has a thickness of 10 to 15 μm.

4. the crosslinkable vinyl monomer includes a monomer having four or more radically polymerizable functional groups selected from the group consisting of a vinyl group, an acryloyl group, and a methacryloyl group, The lithium ion battery according to claim 3, wherein the weight of the crosslinkable vinyl monomer in the protective film is 12 to 18% by weight based on the total weight of the monomers constituting the copolymer and the electrolyte (D).

5. The absolute values ​​of the difference between the SP value of the electrolyte (D) and the SP value of each of the constituent monomers of the copolymer are all 4.9 (cal / cm 3 ) 1/2 4. The lithium ion battery of claim 3, wherein:

6. The lithium ion battery according to claim 3, wherein the weight ratio of the electrolyte (D) in the protective film is 40 to 60% by weight based on the total weight of the monomer constituting the copolymer and the electrolyte (D).

Citation Information

Patent Citations

  • All-solid-state batteries using lithium metal as the anode

    JP2021527936A

  • Lithium metal secondary battery

    JP2023035226A